2021
DOI: 10.1016/j.nicl.2021.102630
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem functional oscillations across the migraine cycle: A longitudinal investigation

Abstract: Highlights Individual migraineurs’ brainstem function alters through the migraine cycle. Functional changes occurred in the 24-hour period immediately prior to a migraine. Greater resting activity variability was found in the SpV, pons and PAG. Increased infra-slow oscillations and regional homogeneity in the SpV and pons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…The brainstem activation in these two phases was also higher than it was during the interictal period. Neuroimaging findings have indicated the cyclic changes in brain activity during different phases of the migraine cycle, corroborating our observations of fluctuating activity [8,[11][12][13][31][32][33]. Increased brainstem activation preceding the migraine attack has been observed after trigeminal nociceptive stimulation [33], after noxious orofacial stimulation [34], and in the resting state [31] and is consistent with enhanced resting-state functional connectivity among brainstem nuclei or between brainstem and cortical regions [13,31].…”
Section: Dynamic Brain Activation During the Migraine Cyclesupporting
confidence: 87%
“…The brainstem activation in these two phases was also higher than it was during the interictal period. Neuroimaging findings have indicated the cyclic changes in brain activity during different phases of the migraine cycle, corroborating our observations of fluctuating activity [8,[11][12][13][31][32][33]. Increased brainstem activation preceding the migraine attack has been observed after trigeminal nociceptive stimulation [33], after noxious orofacial stimulation [34], and in the resting state [31] and is consistent with enhanced resting-state functional connectivity among brainstem nuclei or between brainstem and cortical regions [13,31].…”
Section: Dynamic Brain Activation During the Migraine Cyclesupporting
confidence: 87%
“…The enhanced sensitization of trigeminal and cervical areas observed in the preictal phase 7 could be evaluated as the behavioral consequence of the “activity‐dependent central sensitization” of second‐order neurons in the trigeminocervical complex mediated by the activation of diencephalon and brainstem areas 53 . This is supported by the observation that, during the preictal phase, diencephalon and brainstem areas increase their activation 44,45,60,61 and their functional connectivity with the trigeminocervical complex, 45 which also gradually increases its activity toward the next headache attack 62 …”
Section: Discussionmentioning
confidence: 94%
“…8,24 However, the present data showed consistent evidence of increased widespread sensitization in preictal EM, 7 with reduced mechanical pain threshold over the hand for two different sensory stimulus modalities. The preictal phase is characterized by activation of areas involved in pain processing and in descending modulation of nociceptive input 45,60,61,63 that could become dysfunctional, switching from being antinociceptive to pronociceptive leading to a migraine attack. 2,64-66 However, as other studies showed an increase of endogenous analgesic mechanisms in the preictal phase, 21,67 future longitudinal studies should assess the pain modulation (e.g., conditional pain modulation) 68,69 during the migraine cycle.…”
Section: Widespread Sensitizationmentioning
confidence: 99%
“…Furthermore, future investigations could also focus on changes in brainstem pain circuitry functioning within individual subjects to a greater extent in order to gain a more detailed understanding of changes in system functioning in individuals with chronic neuropathic pain. A similar approach has been used to study changes in brainstem function in individuals with migraine across the migraine cycle ( 31 , 166 ). For instance, it would be valuable to study changes in pain-modulation circuitry functioning over the course of an individual's pain development – from immediately following nerve injury throughout the development and persistence of long-term pain, and to explore whether there are changes in circuitry functioning following the administration of a standard pain treatment.…”
Section: Discussionmentioning
confidence: 99%